How P(H)C is your curriculum? - Bernhard M. Gaede (AOSIS, 2024)
In South Africa and internationally, the alignment of health professions education programme with primary healthcare (PHC) policies is seen to promote the training of fit-for-purpose graduates who can adequately respond to the demands of patient and community needs. This article seeks to describe the development of a tool to assess the degree of PHC in an undergraduate medical curriculum. In defining what is meant by PHC, four dimensions of PHC were identified for the purpose of designing the tool, namely values underpinning PHC, principles of PHC, a generalist focus of the programme, and the level of care that the programme is delivered at. The tool also sought to assess how the content in these dimensions is covered in the curriculum and to which depth students are required to engage. The perspectives that were considered were: what content was being covered, what pedagogy was used, in which context it was being taught and how it was being assessed. For each of these aspects, the dimensions are assessed using an amended Miller's pyramid to assess the expectations of outcomes for the curriculum. The tool is presented and the article reflects on the use of the tool in a process of assessing a medical curriculum.